2010
DOI: 10.1128/jvi.01549-09
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism of CD317 Restriction of Human Immunodeficiency Virus Type 1 (HIV-1) Particle Release and Depletion of CD317 Are Separable Activities of HIV-1 Vpu

Abstract: Vpu antagonizes human immunodeficiency virus type 1 (HIV-1) particle release inhibition by CD317/BST-2/Tetherin. Whether this Vpu activity strictly requires cellular depletion of the restriction factor is unclear. Here, we characterized CD317 variants with mutations in putative sorting or ubiquitination motifs. All mutants still potently impaired release of Vpu-defective HIV-1 and remained sensitive to Vpu-mediated release enhancement. Importantly, this virological antagonism correlated with surface downregula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
83
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(97 citation statements)
references
References 23 publications
13
83
1
Order By: Relevance
“…2, B and C), WT Vpu efficiently down-regulated total levels of the lysine-substituted BST-2 mutant compared with both the control and the Vpu2/6 mutant. This result appears to be in conflict with data reported by Goffinet et al (34), which showed no degradation of the BST-2(K18R/K21R) mutant protein by Vpu. However, those authors also noted that their use of an NH 2 -terminal HA-tagged BST-2 construct transfected into 293T cells led to the accumulation of BST-2 species distinct from K18R,K21R).…”
Section: Vpu-dependent Bst-2 Ubiquitinationcontrasting
confidence: 56%
See 1 more Smart Citation
“…2, B and C), WT Vpu efficiently down-regulated total levels of the lysine-substituted BST-2 mutant compared with both the control and the Vpu2/6 mutant. This result appears to be in conflict with data reported by Goffinet et al (34), which showed no degradation of the BST-2(K18R/K21R) mutant protein by Vpu. However, those authors also noted that their use of an NH 2 -terminal HA-tagged BST-2 construct transfected into 293T cells led to the accumulation of BST-2 species distinct from K18R,K21R).…”
Section: Vpu-dependent Bst-2 Ubiquitinationcontrasting
confidence: 56%
“…Goffinet et al (34) confirmed that a BST-2(K18R,K21R) mutant inhibits viral egress, is sensitive to inhibition by Vpu and can be down-regulated from the cell surface by Vpu. However, unlike WT BST-2, which they observed to be degraded by Vpu, the BST-2(K18R,K21R) protein remained stable in the presence of Vpu, leading them to conclude that Vpu particle release and BST-2 degradation functions are separable (34). Most recently, Tokarev et al (35) have provided the clearest demonstration that BST-2 is ubiquitinated in the presence of Vpu.…”
mentioning
confidence: 99%
“…For the prototypic CD317 antagonist Vpu, downregulation of hCD317 from the cell surface and accelerated degradation have been proposed as key mechanisms (10,15,53). Recent reports (7,12,24) and the current study demonstrate that a reduction of cell-associated CD317 levels is neither sufficient ( Fig. 2A and B) nor required ( Fig.…”
Section: Discussionmentioning
confidence: 67%
“…According to the mechanistic model of a direct physical involvement of CD317 in the process of virion tethering (18,41), its surface levels may be key to its restrictive capacity (12,16,53). Here, we examined the ability of the four viral antagonists to modulate levels of endogenous CD317 on human and mouse cells.…”
Section: Resultsmentioning
confidence: 99%
“…Vpu localizes primarily in endosomes and the trans-Golgi network (4,5), where it is thought to interact with BST-2. Vpu expression results in reduced levels of BST-2 on the host cell membrane (6 -8) and either the degradation (9 -12) or the sequestration of the host factor in intracellular compartments (7,13), leading to increased virus release. BST-2 has been identified as an activator of the NF-B family of transcription factors (14), although the mechanisms by which this occurs and its consequences have remained unknown until very recently.…”
mentioning
confidence: 99%